DNA barcoding of the endangered Aquilaria (Thymelaeaceae) and its application in species authentication of agarwood products traded in the market - Shiou, Yih Lee; Wei, Lun Ng; Mahat, Mohd Noor; Salleh @ Japri, Mohd Nazre; Mohamed, Rozi (Public Library of Science, 2016)
The identification of Aquilaria species from their resinous non-wood product, the agarwood, is challenging as conventional techniques alone are unable to ascertain the species origin. Aquilaria is a highly protected species due to the excessive exploitation of its precious agarwood. Here, we applied the DNA barcoding technique to generate barcode sequences for Aquilaria species and later applied the barcodes to identify the source species of agarwood found in the market. We developed a reference DNA barcode library using eight candidate barcode loci (matK, rbcL, rpoB, rpoC1, psbA-trnH, trnL-trnF, ITS, and ITS2) amplified from 24 leaf accessions of seven Aquilaria species obtained from living trees. Our results indicated that all single barcodes can be easily amplified and sequenced with the selected primers. The combination of trnL-trnF+ITS and trnL-trnF+ITS2 yielded the greatest species resolution using the least number of loci combination, while matK+trnL-trnF+ITS showed potential in detecting the geographical origins of Aquilaria species. We propose trnL-trnF+ITS2 as the best candidate barcode for Aquilaria as ITS2 has a shorter sequence length compared to ITS, which eases PCR amplification especially when using degraded DNA samples such as those extracted from processed agarwood products. A blind test conducted on eight agarwood samples in different forms using the proposed barcode combination proved successful in their identification up to the species level. Such potential of DNA barcoding in identifying the source species of agarwood will contribute to the international timber trade control, by providing an effective method for species identification and product authentication.